Acrostics in Computer Networking Jargon: A Morphosemantic Analysis (International Journal of Scientific Research and Management (IJSRM), 2022)
Acrostics are becoming more and more widespread in computer networking jargon. Most books on computer networking, written in English or French, use them without giving their meanings in order to avoid confusion that may arise in the heads of EFL learners since the form of these acrostics resembles the one of already existing words. This phenomenon needs being tackled since there is not any research related to acrostics used in computer networking jargon. The study uses a corpus of 31 acrostics collected from different books of computer networking. It referred to a morphosemantic approach to analyze these data. Based on the analysis of data, the findings reveal that the acronyms used in computer networking have the same form with some words of English or French. However, there is not any semantic relationship between these words and the acrostics used in the computer networking jargon. Hopefully, this study will help EFL learners/teachers enhance their learning/teaching of English as they are involved in computer networking field.